Pearl millet yields and yield stability under long-term soil fertility management in the Sahel - Aboubacar, D.K.T.I.; Ali, I.; Fatondji, D.; Bado, V.; Ettien, D.J.B. (Wiley, 2022)
Little is known about the impact of long-term fertilizer microdose on pearl millet [Cenchrus americanus (L.) Morrone] yields and yield stability in the Sahel. An 8-yr, long-term experiment evaluated pearl millet yields and yield stability under fertilizer microdose along with crop residues (CRs) management in different plant spacings. Treatments included (a) one absolute control (without fertilizer) and two fertilizer microdose options, (b) 2 g diammonium phosphate fertilizer per planting hole, and (c) 6 g of 15–15–15 (N–P–K) fertilizer per planting hole—under two plant spacings (10,000 and 15,000 pockets ha–1) and with and without CR removal. These were arranged in a randomized complete block design with three replications. A decrease in pearl millet plant spacing (15,000 pockets ha–1) markedly enhanced pearl millet grain yield and total dry matter by 12 and 11%, respectively, vs. the recommended plant spacing (10,000 pockets ha–1). The mean pearl millet grain yields over 8 yr were 470 and 262 kg ha–1 in fertilizer microdose and control plots, respectively. The pearl millet yields increased by 7 and 81% with CR retention in microdose and control plots, respectively, vs. plots with CR removal. Grain yields reductions of 16 and 38% were recorded in fertilizer microdose and control plots, respectively, after 8 yr regardless of CR retention. Fertilizer microdose without CR removal was more stable. However, a considerable decrease in soil N status was observed after 8 yr. These results suggest that fertilizer microdose in combination with CR retention should be used as a base practice for increasing yield in the low-input, pearl millet-based cropping system of the Sahel and similar cropping systems.